2019
DOI: 10.3389/fmicb.2019.02754
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor ArcA Modulates Salmonella’s Metabolism in Response to Neutrophil Hypochlorous Acid-Mediated Stress

Abstract: Salmonella Typhimurium, a bacterial pathogen with high metabolic plasticity, can adapt to different environmental conditions; these traits enhance its virulence by enabling bacterial survival. Neutrophils play important roles in the innate immune response, including the production of microbicidal reactive oxygen species (ROS). In addition, the myeloperoxidase in neutrophils catalyzes the formation of hypochlorous acid (HOCl), a highly toxic molecule that reacts with essential biomolecules, causing oxidative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The analysis of the nucleotide sequence upstream of the macAB operon using Virtual Footprint promoter analysis v.3 ( 65 ) indicated the presence of putative binding sites for global regulators ArcA and OxyR (data not shown). Both transcription factors are known to positively regulate the expression of genes encoding components of the oxidative pathway ( 66 , 67 ). While the exact mechanism of MacAB regulation in S. marcescens is yet to be defined, our results clearly indicate that activation of the macAB promoter is peroxide-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the nucleotide sequence upstream of the macAB operon using Virtual Footprint promoter analysis v.3 ( 65 ) indicated the presence of putative binding sites for global regulators ArcA and OxyR (data not shown). Both transcription factors are known to positively regulate the expression of genes encoding components of the oxidative pathway ( 66 , 67 ). While the exact mechanism of MacAB regulation in S. marcescens is yet to be defined, our results clearly indicate that activation of the macAB promoter is peroxide-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Other redox sensors primarily known to be involved in ROS resistance have also been described in HOCl response in Gram-negative bacteria. These include the two-component system aerobic respiration control (ArcAB) [ 82 , 143 , 144 ], SylA [ 145 ] and OhrR [ 134 ], which are members of the MarR family, PerR, which belongs to the Fur family [ 70 ], and ComR, controlled by the TetR family [ 70 ].…”
Section: Adaptive Response Of Gram-negative Cells To Hoclmentioning
confidence: 99%
“…Previous studies have unveiled that the Arc (aerobic respiratory control) TCS is a key regulatory system facilitating facultative anaerobic bacteria to sense and respond to various respiratory growth conditions and regulate their gene expression accordingly, such as Salmonella enterica serovar Typhimurium, E. coli, Haemophilus parasuis serova 13 clincal strain EP3, and S. enteritidis (Gao et al, 2007;Calderon et al, 2011;Cameron et al, 2013;Jiang et al, 2015;Ding et al, 2016;Basan et al, 2017;Chen and Goulian, 2018;Fernandez et al, 2018;Pardo-Este et al, 2019), as well as regulating virulence factor production, controlling metabolism, chemotaxis, motility and pathogenicity of avian pathogenic E. coli (Jiang et al, 2015), virulence of H. parasuis serovar 13 clinical strain EP3 (Ding et al, 2016), and swarming motility in Serratia marcescens FS14 (Zhang et al, 2018). Similarly, in this study, we demonstrated that ArcBA regulates the virulence traits, bacterial swimming and swarming motility, and gene expression of flagellar in D. oryzae (Figures 3A-C).…”
Section: Discussionmentioning
confidence: 99%